Developing A mobile App for the Rehabilitation of Ankle Sprains - Suzanne McDonough; Christopher Bleakley; Christopher Nugent; Joseph Rafferty; Jonathan Synnott; Adele Boyd; Katie Hunter (Frontiers Media S.A., 2015)
Background: Musculoskeletal injuries are common and costly. Ankle sprains are one of the most common such injuries, carrying significant risk of persistent disabling symptoms. Rehabilitation has been shown to be more effective than standard conservative approaches for musculoskeletal injuries. The use of a mobile app to present rehabilitation guidance may offer a more accessible, engaging and effective solution to ankle sprain rehabilitation. Several existing apps target the prevention and rehabilitation of ankle sprains, however evaluation details are limited. Aim: To develop a mobile phone app that provides interactive, personalised and tailored rehabilitation for people following ankle sprains. Method(s): In order to build requirements and produce content for the app (entitled ReApp 2), relevant literature was reviewed and behaviour change strategies identified from the Behaviour Change Taxonomy (BCT) developed by Michie et al (2013). A flexible and team orientated methodology called Agile was used to refine the technical specification and implemented software using feedback from technical experts (n=5) and clinicians (n=6). Technical experts consisted of participants with at least five years of experience in ICT or a related discipline. These technical experts completed the System Usability Scale (SUS) to rate the usability of the software. The SUS is a widely used usability survey, which provides a single overall score for each participant. These scores can be used to provide comparison between user groups and other software. The clinicians consisted of five physiotherapists and one sport and exercise consultant, all of whom had at least five years of experience in providing rehabilitation treatment for ankle injuries. These clinicians also completed a questionnaire and gave qualitative feedback on the clinical appropriateness of the app. Results: The identified BCTs were prioritised according to clinical importance, technical complexity and time to implement, and video and voice over content was completed. The following strategies were identified to incorporate into the app: modelling of behaviour; monitoring and receiving feedback related to individual behaviour, monitoring and receiving feedback related to the outcome of individual behaviour; and receiving reminders. ReApp 2 received a mean SUS score of 86, which is considerably above the average of 69.69 reported in Bangor et al.'s (2008) review of 2324 surveys from 206 studies. The technical experts indicated that the usability of ReApp 2 was considered to be "excellent" (SUS score over 85.58) by 60% of participants, and "good" by the remaining 40% (SUS score over 72.75). Clinicians agreed or strongly agreed that the clinical content within the app was evidence based (n=3), that the clinical content within the app was suitable for ankle rehabilitation (n=4) and that they would recommend the app to a patient presenting with ankle sprain (n=3). Conclusions: The SUS scores received from the technical evaluation in this project are considerably above average, indicating the excellent-good usability of the app. Clinicians rated the app as evidence based and 50% of clinicians would recommend the app in its current format to patients with ankle sprain.